A Content Analysis of the Komik Seri Pengenalan Anti Gratifikasi Media as Anti-Corruption Character Education for Early Childhood - Masykuroh, Khusniyati; Nisa, Zahrotun (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study analyzes the content of the Komik Seri Pengenalan Anti Gratifikasi, an anti-corruption comic series for early childhood education published by the Ministry of Education and Culture of Indonesia. It addresses the lack of educational media that introduce anti-corruption values to young children. The aim is to identify the character values presented in the comics and evaluate their relevance as tools for character education. The comics are intended to instill core anti-corruption values such as honesty, responsibility, hard work, and caring. Using a descriptive qualitative approach and content analysis, the study examines how these values are conveyed through storylines, characters, dialogue, and illustrations. Data collection was conducted through close reading and detailed note-taking of each comic in the series. Findings indicate that the comics effectively present ethical principles, especially honesty, which is consistently portrayed as a key value in preventing corruption. Through engaging stories and relatable characters, the comics promote positive behaviors like speaking the truth, returning lost items, and admitting mistakes. Responsibility and hard work are also illustrated in scenarios where characters take ownership of their actions and strive to reach their goals. The study highlights the comics’ ability to connect with children through real-life situations, encouraging moral development in an age-appropriate and visual format. This makes abstract values more concrete and easier for early learners to understand. As a result, the comics are deemed adequate for early childhood character education. However, the research also notes the potential to expand the values represented, such as courage and independence, to strengthen the moral message further. Overall, the study supports the use of educational comics as a valuable medium for fostering anti-corruption awareness and building a strong ethical foundation from an early age.